Pengaruh Strategi Bauran Pemasaran Terhadap Perkembangan Ukm Di Dinas Koperasi Usaha Kecil Dan Menengah Kabupaten Bandung - Tiris Sudrartono (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2020)
This research was conducted to find out how much influence the marketing mix strategy has on SMEs development. To find out the obstacles that exist in the marketing mix strategy, and to find out the efforts that can be made by the SMEs development in cooperative anad SMEs in Bandung regency. The research method used in descriptiive quantitative method, the analysis technique used in person product moment analiysis technique with data processing using SPSS V22. The data obtained to explain the results of the study is to distribute questionnaires to 20 question to respondents of 51 respondents from the study sample.The results obtained by the correlation of 0,756 means that it has a strong relationship between the marketing mix strategy variabel the SMEs development variabel with an effect of 57.2 and the remaining 42.8% is influenced by other factors not examined by the aiuthors. The author concludes that the members of SMEs are already good in carrying out markeing mix strategy to develop their business. There are obstacles in efforts to improve the development of SMEs, Such as product quality standards and market access for SMEs products, this is based on the increasinglyWidespread competition of external product with lower prices and quality and market access that is still not broad. The auther’s suggestion in expected that SMEs member can improve product quality and broad market access by building nemerous distribution channel relationships so that the scope of their business is able to develop.